A Comparison of Omega-3 VLC PUFA Content of Premium and Budget Wild Pollock Fish Fingers Manufactured by the Same Producer - Wojciech Kolanowski; Anna Charuta; Joanna Trafiałek (Applied Sciences)
(1) Background: Sea fish with a high level of omega-3 very long-chain (VLC) PUFAs makes them a valuable component of a healthy diet. One of the most popular fish products is fish fingers, for which the market is still growing. The content of omega-3 VLC PUFAs in fish fingers may differ across price categories, such as premium or budget, despite being manufactured from the same fish species. Furthermore, the labelling of fish fingers typically fails to indicate the quantity of omega-3 VLC PUFAs present. It is unclear whether fish fingers can increase the amount of omega-3 VLC PUFAs in the diet. Hence, this study aimed to examine the content of omega-3 VLC PUFAs in pollock fish fingers from premium and budget price categories manufactured by the same producer and sold in supermarkets. (2) Methods: The premium fish fingers were made with pollock fillet and the budget ones with minced pollock meat. Fat content and fatty acids profile were analysed. (3) Results: The primary fatty acid found in fish fingers was oleic acid, followed by linoleic acid. Saturated fatty acids were less than 7%. This reflected the composition of frying fat, which was rapeseed oil. Fish fingers contained a dietary noticeable amount of omega-3 VLC PUFAs; for premium and budget fish fingers it was 283.01 mg and 123.44 mg per 100 g of product, respectively. (4) Conclusions: Not all fish fingers have the same nutritional value, despite being manufactured by the same producer and from the same fish species. Even though both were made from pollock, premium fish fingers were a better dietary source omega-3 EPA and DHA than a low-cost alternative. Eating three sticks (100 g) of examined pollock fish fingers, either premium or budget, can meet the recommended daily intake level of omega-3 VLC PUFAs at 100% or 50%, respectively.